Biological functions of casein kinase 1 isoforms and putative roles in tumorigenesis - Schittek, Birgit (BioMed Central, 2014)
Isoforms of the casein kinase 1 (CK1) family have been shown to phosphorylate key regulatory molecules involved in cell cycle, transcription and translation, the structure of the cytoskeleton, cell-cell adhesion and receptor-coupled signal transduction. They regulate key signaling pathways known to be critically involved in tumor progression. Recent results point to an altered expression or activity of different CK1 isoforms in tumor cells. This review summarizes the expression and biological function of CK1 family members in normal and malignant cells and the evidence obtained so far about their role in tumorigenesis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1476-4598-13-231) contains supplementary material, which is available to authorized users.